International legal standards of professional activity of the lawyer in civil procedure of Ukraine - Шпак, Максим Володимирович (Theory and practice of jurisprudence, 2017)
Of point of view on active implementation of legislative initiatives in national legislation about professional activity of a lawyer especially in civil procedure and also necessary to analysis the international standards of lawyer's activity. Of point of view on active European integration process, nowadays the institute of legal aid is being changed especially due to judicial reform. In this aspect there is an interesting research of the international legislation about professional activity of the lawyer in civil procedure. Scientists are interested in analysis of recent research and publications, also reforming Advocacy in aspect of approximation the national legislation of Ukraine according to international standards. T. B. Vilchyk, V. O. Svyatotska and L. V. Tatsiy researched international and European standards of lawyer's activity. V. V. Komarov, S. S. Bychkova, A. V. Churpyta researched some aspects of the professional lawyer's activity in civil procedure and monographic literature. Paper objective is scientific analysis of the European and international standards of professional activity of the lawyer especially in civil procedure. The author has analyzed the European and international normative documents about the specifics of the professional activity of lawyer including in civil procedure such as: Resolution (78) 8 of the Committee of Ministers on legal aid and consultations on 02.03.1978; Code of Conduct for European lawyers on 28.10.1988 with amendments from 28.11.1988, 6.12.2002, 19.05.2006; General principles for the legal profession. Adopted by the International Bar Association (IBA) 20.09.2006 in Chicago; Basic Principles on the Role of Lawyers on 01.08.1990; Basic Principles on the Role of Lawyers on 07.09.1990; General Code of rules for lawyers in the European Community on 01.10.1988. Author proposed a new article 401 to Civil Procedural Code of Ukraine «Lawyer as a professional representative in the case». In author's opinion, the proposed article must be a logical continuance of reforming professional activity of lawyer especially in civil procedure. In author`s opinion, the European standards of professional lawyer`s activity, particularly in civil procedure are: 1) the legal assistance is provided only by lawyers; 2) high qualification and experience of lawyers as professionals jurists; 3) the privacy and independence of lawyer`s activity; 4) the lawyer executes his professional activities providing the legal assistance to client and should always works in the client`s interests (within the law); 5) the lawyer can get remuneration for professional activities; 6) professional insurance of lawyers; 7) the lawyer should follow the relevant rules about ethical behavior during the providing legal assistance in the courts; 8) honesty and integrity of professional activity; 9) the presence of the corporatism spirit and supporting between the lawyers; 10) respect to all participants in the court; 11) the application of procedural coercion to lawyers when they commit offenses.